Piketty's capital and social policy. (December 2014) - Piachaud, David
Abstract Piketty's Capital (2014) primarily describes and analyses changes in the distribution of wealth and annual incomes. This paper focuses on his policy proposals that make up Part Four of the book. Piketty defends the 'social state' but he discusses it largely in terms of distribution and redistribution between tax units. This neglects the important role of social policy in promoting recognition and redistribution of income and opportunities that is related to gender, race, disability and sexual orientation. Nor does Piketty consider inequalities in health which effect life‐time incomes, nor the impact of housing policies on house prices and the distribution of wealth. It is argued that Piketty's approach to social security is simplistic and plays down the complexity of competing policy goals. On taxation, Piketty defends progressive taxation and proposes a global capital levy. The latter proposal runs into formidable problems in seeking global taxation in a world of nation states. Rather than seeking a policy that is, for the foreseeable future, wholly politically impractical, a case is made for less idealistic but more practical and urgent tax coordination between nations to address the widespread avoidance of taxation that large corporations and the very wealthy are now permitted – taxation on which the future of the social state depends. The importance of human and social capital, which are largely set aside by Piketty, are discussed. Finally, it is argued that his approach to policy is to describe trends and propose amelioration of growing inequality rather than to identify causes of the trends and propose policies that might address the causes. Nevertheless, the importance of his work in bringing issues of inequality to the fore, especially among economists, is recognized and applauded.